2008
DOI: 10.1002/pssb.200844271
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy configuration of δ‐Bi2O3: an ab initio study

Abstract: The oxygen vacancy configurations and electronic structures of δ‐Bi2O3 have been studied using the ab initio calculation full‐potential linearized augmented plane‐wave (FPLAPW) method and considering the relativistic effect in Bi atoms in terms of spin–orbital coupling. Three vacancy structures, 〈111〉, 〈110〉 and 〈100〉, were analysed. It was found that the layered δ‐Bi2O3 with 〈110〉 vacancy alignment is the most stable. An indirect band gap of 0.46 eV was observed for this structure. Additionally, the role of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…To reduce the interaction between the neighboring vacancies, we now consider a supercell of δ-Bi 2 O 3 built by repeating the unit cell of Bi 2 O 3 2×2×2 times. It has been previously shown that the (110) vacancy alignment is the most favorable in δ-Bi 2 O 3 [33]. We have calculated the oxygen vacancy diffusion barriers in different vacancies configurations for one and two vacancies, as shown in figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce the interaction between the neighboring vacancies, we now consider a supercell of δ-Bi 2 O 3 built by repeating the unit cell of Bi 2 O 3 2×2×2 times. It has been previously shown that the (110) vacancy alignment is the most favorable in δ-Bi 2 O 3 [33]. We have calculated the oxygen vacancy diffusion barriers in different vacancies configurations for one and two vacancies, as shown in figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the thickness of surface oxide layers is much lower (of the order of nanometers for SiO 2 on Si [5152]). In our case it is increased by the electric field and good oxygen mobility in BiO x due to the formation of charged Bi vacancies [5960].…”
Section: Resultsmentioning
confidence: 99%
“…Similar vacancy ordering has also been observed in neutrondiffraction experiments [7] conducted on rare-earth-doped δ-Bi 2 O 3 . Extensive research has been performed in identifying the lowest energy vacancy-ordered structure of δ-Bi 2 O 3 , and <100> [8][9][10], <110> [11] or <111> [12] vacancyordering models have also been proposed. We have shown from first-principles calculations that <110>-<111> model is the lowest energy model among either of <100>, <110>, or <111>.…”
Section: Introductionmentioning
confidence: 99%